Universal Target Capture of HIV Sequences From NGS Libraries - Yamaguchi, Julie; Olivo, Ana; Laeyendecker, Oliver; Forberg, Kenn; Ndembi, Nicaise; Mbanya, Dora; Kaptue, Lazare; Quinn, Thomas C.; Cloherty, Gavin A.; Rodgers, Mary A.; Berg, Michael G. (Frontiers in Microbiology, 2018)
Background Global surveillance of viral sequence diversity is needed to keep pace with the constant evolution of HIV. Recent next generation sequencing (NGS) methods have realized the goal of sequencing circulating virus directly from patient specimens. Yet, a simple, universal approach that maximizes sensitivity and sequencing capacity remains elusive. Here we present a novel HIV enrichment strategy to yield near complete genomes from low viral load specimens. Methodology A non-redundant biotin-labeled probe set (HIV-xGen; n=652) was synthesized to tile all HIV-1 (groups M, N, O, and P) and HIV-2 (A and B) strains. Illumina Nextera barcoded libraries of either gene-specific or randomly primed cDNA derived from infected plasma were hybridized to probes in a single pool and unbound sequences were washed away. Captured viral cDNA was amplified by Illumina adaptor primers, sequenced on a MiSeq, and NGS reads were demultiplexed for alignment with CLC Bio software. Results HIV-xGen probes selectively captured and amplified reads spanning the entirety of the HIV phylogenetic tree. HIV sequences clearly present in unenriched libraries of specimens but previously not observed due to high host background levels, insufficient sequencing depth or the extent of multiplexing, were now enriched by >1000 fold. Thus, xGen selection not only substantially increased the depth of existing sequence, but also extended overall genome coverage by an average of 40%. We characterized 50 new, diverse HIV strains from clinical specimens and demonstrated a viral load cutoff of approximately log 3.5 copies/ml for full length coverage. Genome coverage was <20% for 5/10 samples with viral loads < log 3.5 copies/ml and >90% for 35/40 samples with higher viral loads. Conclusions Characterization of >20 complete genomes at a time is now possible from a single probe hybridization and MiSeq run. With the versatility to capture all HIV strains and the sensitivity to detect low titer specimens, HIV-xGen will serve as an important tool for monitoring HIV sequence diversity.